Re-framing the status of narrative in family business research: Towards an understanding of families in business. Issue 1 (March 2017) - Hamilton, Eleanor; Discua Cruz, Allan; Jack, Sarah
Highlights: This study argues that narratives help researchers focus on the interconnection between family and business strategy. Narrative research provides insight into topics such as collective identities, emotions, legacy and the dark side of families in business. This study offers practical guidelines when researching the strategies behind the creation, development and continuity of a family firm. Abstract: This article will emphasize the status and relevance of narrative research in the study of families in business and family business strategy. It argues that narratives can provide a better understanding of the intricate connections between family and business and across family generations in business. Narratives generate knowledge by helping to shape a collective identity and as a form of intergenerational communication. By focusing on narratives as a phenomenological inquiry, we argue that interviews allow researchers to engage often in emotionally charged and intimate conversations with individuals that want to talk about experiences as members of a family business. This paper will discuss the usefulness of narrative approaches for family business strategy research, develop a catalogue of research questions for exploration, highlight challenges and offer solutions to deal with them when using narrative methods in family business research. This paper argues that while several challenges may be encountered, narratives allow researchers to delve into the intricate lives of members of a family in business.